Reinforcing Myths About Women in Philippine Culture: Semiotic Analyses of the Sexbomb Girls in Eat Bulaga's Laban o Bawi - Mendoza, Trina Leah (Archīum Ateneo, 2024)
Movie and TV stars are an influential part of Philippine society. Not only do they entertain audiences with their television shows or movies, but their private lives and actions are arguably as interesting to the public. Celebrities and stars are admired, idolized, and looked up to by many of their followers, such that their values and actions can greatly influence their fans. However, their images may hold various meanings that are not evident to many people. This study analyzes a group of unconventional stars that changed the landscape of noontime viewing—the Sexbomb Girls—using a semiotic approach. It seeks to reveal the different images of women portrayed by the Sexbomb Girls, and understand how media can reinforce myths. The Sexbomb Girls were a social phenomenon and a product of production that depicted binary oppositions and metaphors: virgin/vamp, loud woman, and ordinary woman. These signs, binary oppositions, and metaphors served as myths that naturalized, influenced, and reinforced sexy female background dancers into becoming an ordinary part of noontime and game shows. Because they appeared six days a week in Eat Bulaga, the Sexbomb Girls have desensitized the Filipino masses such that seeing sexily clad background dancers in these shows has become ordinary and acceptable.